Comorbidities and Complications of Cerebral Palsy - Imms, Christine; Cooper, Monica S (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on treating the associated comorbidities and complications of cerebral palsy. Increased prescription of technology means that we are treating some comorbidities of cerebral palsy earlier or even pre-emptively. Increased life expectancy, compared with 20 years ago, means that we are also seeing even later complications of cerebral palsy. However, increased access to intensive medical care at home, non-invasive ventilation, and total parenteral nutrition now exist. There is also greater engagement with the perspectives and expectations of parents/carers and children. As society begins to discuss mental health more openly, we are also starting to recognise the significant two-way associations between disability and mental health. Ethical consultation may be warranted when harm with treatment exceeds the benefit. As we prepare children with cerebral palsy for adulthood, there is more thought and discussion around issues such as pain, mental health, quality of life, independence, and participation. Researchers in the field of cerebral palsy have contributed original articles and reviews which help build our evidence base to guide shared decision making.